(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2017)
Career building is the most cherished part of every engineering student. For an engineering graduate it is necessary to have immense knowledge in their domain to get placed in a reputed company. Data Mining is used to gain knowledge, find the hidden information and also this system applies data mining techniques to the academic dataset. The Academic data includes the Internal (CCET 1, CCET2 and CCET3) marks and the Assignment marks. The final semester marks are predicted from the analyzed result of each student. In order to increase the accuracy, this system introduces reweight enhanced boosting algorithm.